Against evidence-based oppression: Marginalized youth and the politics of risk-based assessment and intervention. (May 2017) - Goddard, Tim; Myers, Randolph R
Actuarial risk/needs assessments exert a formidable influence over the policy and practice of youth offender intervention. Risk-prediction instruments and the programming they inspire are thought not only to link scholarship to practice, but are deemed evidence-based. However, risk-based assessments and programs display a number of troubling characteristics: they reduce the lived experience of racialized inequality into an elevated risk score; they prioritize a very limited set of hyper-individualistic interventions, at the expense of others; and they privilege narrow individual-level outcomes as proof of overall success. As currently practiced, actuarial youth justice replicates earlier interventions that ask young people to navigate structural causes of crime at the individual level, while laundering various racialized inequalities at the root of violence and criminalization. This iteration of actuarial youth justice is not inevitable, and we discuss alternatives to actuarial youth justice as currently practiced.